Determinants of Return on Equity in Regional Banks: An Empirical Study from the Special Region of Yogyakarta - Agus Tri Basuki (KENDALI: Economics and Social Humanities, 2025)
This study aims to examine the influence of BOPO (Operational Expenses to Operational Income), NIM (Net Interest Margin), LDR (Loan to Deposit Ratio), GWM (Statutory Reserves), and KPMM (Capital Adequacy Ratio) on ROE (Return on Equity) at the Regional Development Bank of the Special Region of Yogyakarta. The research utilizes quarterly data obtained from the Financial Services Authority (OJK) spanning from March 2017 to December 2024. A multiple linear regression approach is employed to analyze the relationship among the variables. The results indicate that BOPO, GWM, and KPMM have a statistically significant negative effect on ROE. In contrast, NIM exerts a significant positive effect on ROE, while LDR shows no significant influence. Based on these findings, bank managers are advised to implement strategic policies aimed at improving efficiency by reducing operational costs (BOPO), optimizing reserve fund allocations (GWM), and maintaining a balanced capital structure (KPMM). Additionally, increasing NIM through better interest rate management can enhance profitability. Monitoring and controlling these financial ratios effectively will support sustainable financial performance and maximize shareholder value.